Pemanfaatan Facebook Pro sebagai Sumber Pendapatan Digital bagi Kreator Pemula: Studi Reflektif Berbasis Pengalaman Pribadi - Muhammad Arjun; Wa Ode Rayyani (CV. ITTC INDONESIA, 2025)
This study aims to explore how novice content creators utilize the monetization feature of Facebook Pro as a source of digital income. Using an autoethnographic qualitative approach, the researcher reflects on personal experiences while also including data from other beginner creators. The findings reveal that digital monetization often begins unintentionally but develops into a consistent strategy through learning and adaptation. Key strategies include regular posting, exploring relevant content themes, understanding the algorithm, and leveraging peer communities. Challenges include limited digital literacy, unstable internet access, psychological pressure, and algorithmic uncertainty. This study highlights the transformative meaning of social media as a productive space and offers insights for new creators and digital platform developers.